1971
DOI: 10.2134/agronj1971.00021962006300030042x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Spectral Properties of Leaves with Special Emphasis on Leaf Water Status1

Abstract: Leaf structure and water content constitute major factors affecting the interaction of radiant energy with leaves in the wavelength region from 800 to 2,600 mµ. Reflectivity, Rλ, and transmissivity, T», were measured in this wavelength region for leaves from three crop species (corn, Zea mays; soybean, Glycine max; sorghum, Sorghum bicolor). Absorptivity, Aλ, was calculated from measurements of Rλ and Tλ. The spectral responses (R», Tλ, or Aλ ) at six wavelengths (maxima and minima of the reflectivity curve) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

1975
1975
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(13 citation statements)
references
References 2 publications
0
11
0
2
Order By: Relevance
“…Live fuel moisture content is the moisture level (expressed in percentage) found in grass, brush and trees. Related theory, linking plant moisture to its spectrum, was forged by Gates et al (1965), Knipling (1970), Carlson et al (1971) and Thomas et al (1971), among others. Their historical experiments documented that leaf chloroplasts absorb highly in the red (0.6-7.0 lm); that leaf water absorbs in the middle infrared (1.3-2.7 lm); and that near-infrared reflectance was mediated by cell structure (Figure 1).…”
Section: The Spectral Basis For Variations In Live Fuel Moisture Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Live fuel moisture content is the moisture level (expressed in percentage) found in grass, brush and trees. Related theory, linking plant moisture to its spectrum, was forged by Gates et al (1965), Knipling (1970), Carlson et al (1971) and Thomas et al (1971), among others. Their historical experiments documented that leaf chloroplasts absorb highly in the red (0.6-7.0 lm); that leaf water absorbs in the middle infrared (1.3-2.7 lm); and that near-infrared reflectance was mediated by cell structure (Figure 1).…”
Section: The Spectral Basis For Variations In Live Fuel Moisture Contentmentioning
confidence: 99%
“…Related theory, linking plant moisture to its spectrum, was forged by Gates et al. (1965), Knipling (1970), Carlson et al. (1971) and Thomas et al.…”
Section: Introductionmentioning
confidence: 99%
“…Studies involving plant canopies use data obtained with hand-held radiometers and aircraft or spacecraft sensors (Thompson and Wehmanen 1979, McDaniel and Haas 1982, Jackson and Ezra 1985, Rock et al 1985, Hunt et al 1987. Those concentrating on individual leaves, or a collection of leaves, use data obtained in a laboratory with spectrophotometers or hand-held radiometers (Weber and Olson 1967, Carlson et al 1971, Thomas et al 1971, Guyot et al 1984, Ripple 1986, Hunt et al 1987b. Given an emphasis on leaf reflectance studies, the question arises as to whether the spectral response ofleaves to water stress is a good indicator of the response of plant canopies to water stress?…”
Section: Problemmentioning
confidence: 99%
“…Leaf water content directly affects leaf reflectance and transmittance since water absorption bands exist in the 1.35-2.5 11m region (Gausman et al 1971b). Relative water content accounted for 80% of the leaf reflectance in 1.45, 1.95, and 2.2 11m using a linear regression technique (Carlson et al 1971).…”
Section: Leaf Water Contentmentioning
confidence: 99%
“…The greatest change in mid-IR reflectance from cotton leaves occurred when the relative turgidity went below 70% and water stress or leaf wilting was visible on plants. Carlson et al (1971) reported that an approximate 4% change in reflectance could result from a 10% change in relative water content. They statistically accounted for more than 80% of the variability in reflectance at 1.45, 1.95, and 2.2 f..lm in corn, soybean, and sorghum with relative water content.…”
Section: Water Stressmentioning
confidence: 99%